Water lilies as emerging models for Darwin's abominable mystery. (4th October 2017) - Chen, Fei; Liu, Xing; Yu, Cuiwei; Chen, Yuchu; Tang, Haibao; Zhang, Liangsheng
Abstract: Water lilies are not only highly favored aquatic ornamental plants with cultural and economic importance but they also occupy a critical evolutionary space that is crucial for understanding the origin and early evolutionary trajectory of flowering plants. The birth and rapid radiation of flowering plants has interested many scientists and was considered 'an abominable mystery' by Charles Darwin. In searching for the angiosperm evolutionary origin and its underlying mechanisms, the genome of Amborella has shed some light on the molecular features of one of the basal angiosperm lineages; however, little is known regarding the genetics and genomics of another basal angiosperm lineage, namely, the water lily. In this study, we reviewed current molecular research and note that water lily research has entered the genomic era. We propose that the genome of the water lily is critical for studying the contentious relationship of basal angiosperms and Darwin's 'abominable mystery'. Four pantropical water lilies, especially the recently sequenced Nymphaea colorata, have characteristics such as small size, rapid growth rate and numerous seeds and can act as the best model for understanding the origin of angiosperms. The water lily genome is also valuable for revealing the genetics of ornamental traits and will largely accelerate the molecular breeding of water lilies. Abstract : Plant evolution: Advancing the abominable As one of the first diverging branches of flowering plants, waterlilies, beautiful aquatic flowers, may hold the key to the origin of these remarkable organisms. The rise of the angiosperms (flowering plants) occurred suddenly, rapidly and mysteriously, prompting Charles Darwin to term it an 'abominable mystery.' Liangsheng Zhang and colleagues at Fujian Agriculture and Forestry University, Fuzhou, China, review how recent advances in genetic and genomic studies have narrowed down the first branching groups of the angiosperm family tree to three groups: a small New Caledonian tree, Amborella, a group of about 100 woody plant species known as Austrobaileyales, and the waterlilies. However, precise relationships among these groups remain unclear. The first waterlily genome to be sequenced will have great potential to shed light on the origin of angiosperms, as well as contribute to tools for breeding ornamental waterlilies.